PENGARUH RELATIONSHIP MARKETING TERHADAP KEPUASAN MAHASISWA UNIVERSITAS TOMPOTIKA LUWUK BANGGAI - Fadil Mustafa (AkMen JURNAL ILMIAH, 2012)
The results of the analysis thitung probability value of 6.771 to 0.000 is smaller than 0.05. The variable social benefits significantly influence student satisfaction because thitung> ttable and besides Probability <a 0.05. Variable functional benefits have significant impact because ttable tcount = 3.296 = 1.658 and the probability value of 0.001. Thus thitung> ttable and Probability <a 0.05, it can be said that the functional benefit significantly influence student satisfaction